Processos de aprendizagem e criação em danças afroancestrais: proposições pedagógicas e modos de fazer - Sousa, Gerson Carlos Matias de (2018)
My dissertation proposes to share pedagogical propositions of teaching-learning-creation in Afro-Canadian dances, resulting from experiments and systematizations of corporal exercises developed with / by educators in public schools, artistic groups / companies and cultural projects, in the extension course: "Afro-American corporations in the contemporary scene", where I used the methodological bases of teaching constructed by Cia Balé Baião in the Culture Point Galpão da Cena, Itapipoca CE and the principles of Pretagogy, a theoretical-methodological framework developed by Sandra Petit together with NACE Nucleus of the Africanities of Ceará / NACE-UFC). The course made possible the experience and cataloging of exercises and didactic corporal games that empower the educator to dance in an effective and integral way with the transdisciplinary practices of Afro-Canadian dances in a formal and non-formal educational context, assuming a posture of an active subject who dances along with the students, witnessing to the body their own African dance singularities and enabling dance to be a continuous educational experience favorable to the development of the dancing autonomy of all bodies, breaking with the Eurocentric concept that is limited to the training or reproduction of steps to be followed and reproduced. For Paulo Freire (2000), a process of teaching-learning does not constitute with "transfers of knowledge" or "mechanical repetitions". The research built throughout the course generated experiences of empowerment and emancipation of the educators to the extent that they allowed themselves to dance their personal myths, their life histories, memories, desires, hopes and militants through their singularities and bodily subjectivities, experiencing Being in community, Being in connection with each other / different dance. In this investigative route the following questions were superimposed: What pedagogical propositions and / or dancing practices can contribute to the African-American reconnection of the contemporary body? In what ways can African-Brazilian dances contribute to teaching-learning-creation processes in the contexts of formal and non-formal education?